Hak Waris Anak Di Luar Nikah: Perbandingan Hukum Islam Dan Hukum Perdata - Hidayatallah, Faizal; Medica Aulya A., Shafira; Novitasari, Dian (UNIVERSITAS SERAMBI MEKKAH, 2025)
Children born out of wedlock often face legal challenges related to their status and rights, particularly inheritance rights. This study aims to analyze how Islamic law and civil law regulate the inheritance rights of children born out of wedlock in Indonesia. The research method used is library research, which involves reviewing academic works and literature discussing the inheritance rights of children born out of wedlock under Islamic inheritance law and civil law. Based on the analysis of Islamic law and the applicable civil regulations in Indonesia, this study identifies differences in the regulation of inheritance rights for children born out of wedlock. In Islamic law, children born out of wedlock only have a nasab (lineage) connection with their mother and her family, while under civil law, a child recognized by their biological father may inherit from the father's side. The main difference lies in the recognition of nasab by the biological father, whether voluntarily or through legal procedures. Although there is commonality in the regulation of inheritance from the mother, the regulation of inheritance rights from the biological father needs further adjustment to ensure fairness and comprehensive protection of children's rights.